TINGKAT KESEGARAN JASMANI SISWA EKSTRAKURIKULER FUTSAL SMA NEGERI 1 KAMPAR - Makhfuz, Abdul (Pusat Pengembangan Olahraga Universitas Pahlawan, 2024)
This study aims to determine the level of physical fitness of futsal extracurricular students at SMA Negeri 1 Kampar. This type of research is descriptive quantitative. The instrument used in this study was the Indonesian Physical Fitness Level (TKJI) test, namely running 60 meters, lifting the body 60 seconds, lying down for 60 seconds, jumping upright and running 1200 meters. Then the data is processed with statistics. The results of data analysis in this study showed that the physical fitness level of students was classified as good with a presentation of 0% as many as no student reached this classification, moderate classification with a percentage of 16,66%, there were 2 student who reached this classification with a presentation of 75% as much as 9 students. After processing the data with statistics, the level of physical fitnesss of the futsal extracurricular students at SMA Negeri 1 Kampar with an average value of 75% is located in the 10-13 interval so it lies in the lack of classification. Keyword: Physical Fitness Level